The effects of different training programs on sleep and academic performance of senior high school boy students: a randomized controlled trial - Zhao, Yueming; Li, Guangxin; Zou, Zhikang; Zhang, Xin; Hou, Shilun (Frontiers in Psychology, 2025)
ObjectiveTo explore the effects of different physical training programs on the sleep of boy students in a senior high school, and to provide a reference for effectively improving the sleep level of students in a senior high school, as well as optimizing the physical training program.Methods77 boys in 11th grade of a senior high school were randomly divided into four groups: Group I (traditional training), Group II (strength training), Group III (HIIT training), and Group IV (strength +HIIT training). At the points before and after the intervention, the Pittsburgh Sleep Quality Index (PSQI) and examination scores were measured as indicators of the sleep health and academic performance of students in senior high school, and the intervention effects of different schemes were compared.Results(1) After the intervention, the PSQI global score of Group II, Group III, and Group IV was significantly lower than that of Group I (p < 0.001, p = 0.004, p = 0.01, respectively), and the PSQI global score (p < 0.001, p = 0.02, p < 0.001, respectively), sleep latency (p = 0.008, p = 0.003, p = 0.005, respectively) and sleep duration (p < 0.001, p = 0.005, p = 0.003, respectively) were significantly lower than those before intervention; (2) After intervention, the score of sleep disturbances of Group IV was significantly lower than that before intervention (p = 0.02); (3) After the intervention, academic performance among the four groups show no significance (p = 0.886 > 0.05), while Group IV was significantly higher than that before intervention (p = 0.047).ConclusionCompared with traditional training programs, strength training, HIIT and strength+HIIT training programs have a stabilizing and improving effect on the sleep health level of senior high school boy students, mainly reflected by reducing sleep latency and increasing sleep duration. All four training programs can improve academic performance, while the strength+HIIT training program produced a more significant effect.